Process and effect evaluation of the app-based parenting program Samen Happie! on infant zBMI: A randomized controlled trial - Karssen, Levie T.; Larsen, Junilla K.; Burk, William J.; Kremers, Stef P. J.; Hermans, Roel C. J.; Ruiter, Emilie L. M.; Vink, Jacqueline M.; de Weerth, Carolina (Frontiers in Public Health, 2022)
Background Although energy balance-related parenting practices are regarded critical components in the prevention of childhood obesity, most programs targeting parenting practices with respect to a wide range of energy balance-related behaviors were not aimed at high-risk families with a lower socioeconomic position (SEP). Objective The Samen Happie! app-based program aimed to stimulate healthy child weight development especially among families with a lower SEP, by encouraging healthy energy balance-related parenting practices. Methods A two-armed randomized controlled trial examined the process and effectiveness of the Samen Happie! program on child zBMI outcomes at 6- and 12-months follow-up. In total, 357 Dutch parents with infants aged 5–15 months old at baseline participated. Parents in the app condition (n = 179) received access to the Samen Happie! app and were compared to a waitlist-control condition (n = 178). Changes in zBMI were examined through linear mixed-effects models based on intention-to-treat and exploratory per-protocol principles. Results Process data showed low levels of sustained app use and moderate app acceptability. A general increase in child zBMI was observed in both conditions after 6 and 12 months. Intention-to-treat analyses using multiple imputations showed several statistically significant differences between conditions and high-risk subgroups. Specifically, at 6-months follow-up, zBMI increase was least pronounced in the app condition among children of parents with lower educational level. These findings were supported by exploratory per-protocol analyses including only frequent app users. In addition, per-protocol analyses showed benefits of app use at 6-months follow-up for children of parents with higher BMI. However, these effects were reversed at 12-months follow-up in both intention-to-treat and per-protocol analyses, where children of parents in the app condition in general increased the most in zBMI. Conclusions This study suggests that the Samen Happie! program might prevent zBMI increases after 6 months among children of parents with lower educational level, and children of parents with higher BMI who more frequently use the app. However, the app did not prevent increases in zBMI after 12 months. Future research should investigate strategies to increase sustained app use and engagement in mHealth parenting programs for childhood obesity as well as options to combine app-based programs with additional support strategies aimed at high-risk families. Trial registration Netherlands trial register (ID: NTR6938), https://trialsearch.who.int/Trial2.aspx?TrialID=NTR6938.